Diversity of bats (Mammalia, Chiroptera) in the Parque Estadual de São Camilo, Paraná, Southern Brazil - Rocha Ribas, Mateus; Batista, Sara Cristina; Rocha Aranha, José Marcelo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2023)
The Parque Estadual de São Camilo (PESC) is one of the few forest fragments in the western Paraná, Southern Brazil, a region with a high agricultural activity. The objective of this study was to survey bat species in this park and determine the significance of this area for conservation of bat species. Samples were collected during four nights per month from September 2016 to August 2017, using mist nets placed at eight different sites in the PESC. A total of 380 individuals of three families and 12 species were captured. The most frequent and constant species were Artibeus lituratus, Sturnira lilium, and Artibeus fimbriatus. The most frequent dietary guild found was frugivorous, followed by insectivorous, omnivorous, and carnivorous. A higher species abundance was found in sites at the forest fragment edge. Two Phyllostominae species, Chrotopterus auritus and Phyllostomus hastatus, were found only in the interior of the forest fragment. Although no endangered bat species were identified, the preservation of forest areas in secondary succession, can benefit species that depends on conserved areas. Finally, we recommend conducting new studies within the park, with particular emphasis on unexplored areas, to shed light on the ecology and population dynamics of bats in PESC.
Keywords: Chiropterofauna; Semideciduous seasonal forest; Protected areas; Atlantic Forest